1993
DOI: 10.1002/1097-0142(19930915)72:6<1827::aid-cncr2820720606>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoid adenocarcinoma of the stomach. A clinicopathologic and immunohistochemical analysis

Abstract: Background. The clinicopathologic and immunohistochemical features of the primary gastric hepatoid adenocarcinomas still remain unclear. Methods. The authors evaluated 28 hepatoid adenocarcinomas (HC) of the stomach on the basis of characteristic histologic features resembling hepatocellular carcinoma, which were selected from the 7200 cases of primary gastric carcinoma in their files. Additionally, 22 alpha‐fetoprotein (AFP)‐positive adenocarcinomas without hepatoid features (APC) were also selected. Results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
178
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(187 citation statements)
references
References 18 publications
7
178
2
Order By: Relevance
“…toyoda et al reported that it is difficult to determine whether an endometrial tumor produces AFP solely on the basis of the morphological features of the tumor (9). nagai et al reported cases of Hcs and AFP-positive adenocarcinomas without heparoid features (APc) of the stomach (16). the incidence of venous invasion in Hc was higher than that of APC.…”
Section: Discussionmentioning
confidence: 99%
“…toyoda et al reported that it is difficult to determine whether an endometrial tumor produces AFP solely on the basis of the morphological features of the tumor (9). nagai et al reported cases of Hcs and AFP-positive adenocarcinomas without heparoid features (APc) of the stomach (16). the incidence of venous invasion in Hc was higher than that of APC.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have described the histological features of AFP-GC (20,(27)(28)(29). In 1981, Kodama et al described two histological types of AFP-GC based on immunohistochemical staining, consisting of a medullary type characterized by polygonal cells arranged in solid nests or sheets, and a well-differentiated papillary or tubular type, with clear cytoplasm (27).…”
Section: Discussionmentioning
confidence: 99%
“…To discriminate between non-hepatoid adenocarcinoma and hepatoid adenocarcinoma of the stomach, the measurement of AFP isoforms is also useful, and hepatoid adenocarcinoma of the stomach demonstrates a liver-type binding pattern with the lectin concanavalin A (29). Nagai et al proposed a novel definition, that the diagnosis of AFP-GC may be based on characteristic histological features (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations